2022
DOI: 10.1038/s41575-022-00605-x
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiome as a modulator of healthy ageing

Abstract: The gut microbiome is a contributory factor in ageing-related health loss and in several non-communicable diseases in all age groups. Some age-linked and disease-linked compositional and functional changes overlap, while others are distinct. In this Review, we explore targeted studies of the gut microbiome of older individuals and general cohort studies across geographically distinct populations. We also address the promise of the targeted restoration of microorganisms associated with healthier ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
185
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(203 citation statements)
references
References 210 publications
(166 reference statements)
14
185
2
2
Order By: Relevance
“…Given its involvement in the aging process and its contribution to the regulation of immune response and metabolic homeostasis, the intestinal microbiota has been postulated as a possible biomarker of healthy aging [12,17,18]. In fact, the ability of eubiosis to contrast inflammation, alterations in intestinal permeability, as well as the decline of both cognitive and bone health, is well known [19].…”
Section: Introductionmentioning
confidence: 99%
“…Given its involvement in the aging process and its contribution to the regulation of immune response and metabolic homeostasis, the intestinal microbiota has been postulated as a possible biomarker of healthy aging [12,17,18]. In fact, the ability of eubiosis to contrast inflammation, alterations in intestinal permeability, as well as the decline of both cognitive and bone health, is well known [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, centenarians are generally regarded as a biological model of thriving aging due to their ability to live in a somewhat good state of health for several decades. [18,19]. For several studies have pointed out that the composition of the GM of centenarians of various ethnicities and geographical positions presents a high biodiversity and representation of Firmicutes, Bifidobacterium, as well as SCFA producers, with their respective anti-inflammatory and homeostatic properties, when compared with the elderly or younger adults [20][21][22], supports the concept that gut microbiota behavior does not reflect chronological but biological aging [18].…”
Section: The Role Of the Aging Process And Exercise Training On Intes...mentioning
confidence: 76%
“…Retaining a high Bacteroides dominance into older age can predict decreased survival in a four-year [18]. Ghosh et al [19] reported that the typical aging-related alterations are typified by a loss of dominant commensal taxa (such as Prevotella, Faecalibacterium, Eubacterium rectale, Lachnospira, Coprococcus, and the health-associated genus Bifidobacterium). Furthermore, these taxa seemed to be replaced by a second group of commensals (such as the putatively beneficial Akkermansia, Christensenellaceae, Butyricimonas, Odoribacter and Butyricicoccus) and pathobionts (Eggerthella, Bilophila, Fusobacteria, Streptococcus, and Enterobacteriaceae).…”
Section: The Role Of the Aging Process And Exercise Training On Intes...mentioning
confidence: 99%
“…Finally, changes in the intestinal microbiome in the aged population could also be a factor in the heighted intestinal response to burn injury with age. Evidence in elderly humans and in rodent models of aging show that, even in the absence of injury, there are dramatic changes in fecal microbiota relative to younger subjects (reviewed in [ 64 - 68 ]. In humans, aging often correlates with a decline in bacterial diversity, especially in the context of frailty and unhealthy aging [ 69 - 72 ].…”
Section: Poor Outcomes After Burn Injury In the Aged Population: Does...mentioning
confidence: 99%